2005
DOI: 10.1016/j.femsle.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

RelA alone appears essential for (p)ppGpp production whenNeisseria gonorrhoeaeencounters nutritional stress

Abstract: The bacterial stringent response is a pleiotrophic physiological response that is evoked when bacteria are subjected to nutrient stress and is mediated through the accumulation of hyperphosphorylated guanine nucleotides ((p)ppGpp) which are synthesized by the combined action of the relA and spoT gene products. The relA and spoT genes were cloned from Neisseria gonorrhoeae strain MS11 and various insertional and deletion mutants were constructed. Deletion of the gonococcal relA gene abrogated the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In this study, we have identified a global regulatory system that plays a role in F. novicida virulence, where a relA mutant had reduced survival in macrophage-like cells, and was attenuated more than 100-fold in a BALB/c mouse model. We also confirmed that the reduced virulence observed was not a result of a growth defect, as has been described for other (p)ppGpp-deficient mutants (Fisher et al, 2005;Lemos et al, 2004;Okada et al, 2002). Uptake of F. novicida U112 DrelA : : cam into murine macrophages was similar to that of the wild-type and indicates that RelA is not involved in immune cell invasion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, we have identified a global regulatory system that plays a role in F. novicida virulence, where a relA mutant had reduced survival in macrophage-like cells, and was attenuated more than 100-fold in a BALB/c mouse model. We also confirmed that the reduced virulence observed was not a result of a growth defect, as has been described for other (p)ppGpp-deficient mutants (Fisher et al, 2005;Lemos et al, 2004;Okada et al, 2002). Uptake of F. novicida U112 DrelA : : cam into murine macrophages was similar to that of the wild-type and indicates that RelA is not involved in immune cell invasion.…”
Section: Discussionsupporting
confidence: 88%
“…The role of (p)ppGpp in Francisella appears to be complex, as disruption of the relA gene did not result in a reduced growth rate, a stationary phase defect or reduced biofilm formation, as reported in other bacteria (Fisher et al, 2005;Lemos et al, 2004;Okada et al, 2002). Many basic questions remain unanswered as to how (p)ppGpp exerts its effects, but it is thought that (p)ppGpp acts at the level of transcription, targeting RNA polymerase (Potrykus & Cashel, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The relA-mediated SR to nutrient limitation has been shown to affect virulence and quorum-sensingrelated phenotypes in several gram-negative bacteria (14,16,17,23). PCR screening of the arrayed SCRI1043 mutant bank failed to identify any mutants carrying insertions in the relA gene.…”
Section: Resultsmentioning
confidence: 99%
“…cluster next to the gammaproteobacterial branch (30). ppGpp production has been described for Neisseria gonorrhoeae (20). In contrast to E. coli, the gonococcal SpoT protein does not seem to contribute to ppGpp production, and a relA single mutant had a growth defect on rich solid medium.…”
Section: Discussionmentioning
confidence: 99%